2022-RA-1339-ESGO Treatment outcome of gestational trophoblastic disease at single center of Saudi Arabia. (20th October 2022) - Alghamdi, Jawaher Saeed; Azam, Faisal; Hakami, Ahamad; Alselwi, Waleed; Sefiane, Samia
Abstract : Introduction/Background: Gestational trophoblastic disease (GTD) constitutes rare group of benign and malignant neoplasia with high cure rates. This study is aimed to evaluate the treatment outcomes in our population Methodology: Retrospective analysis of patients treated with chemotherapy for GTD at King Fahad specialist Hospital Dammam from January 2016 till May 2022. Clinical data were collected from patients electronic files Results: A total of 24 patients with GTD received chemotherapy. Median age was 32 (18–51) years. According to FIGO scoring system, most patients were low-risk (n=21, 87.5%). All patients had histological diagnosis with most common type as complete mole in 13 (54%) patients followed by partial mole (n=7, 29%), choriocarcinoma (n=3, 13%) and epithelioid trophoblastic tumour (n=1, 4%). Median serum BHCG before starting chemotherapy was 54000 (133–949117)mIU/ml. Intramuscular Methotrexate (IM-MTX) was used as a first-line chemotherapy in 20 patients with low-risk disease. It was administered in either weekly (n=9, 45%) or 14 days regimen (n=11, 55%). One patient received actinomycin because of contra-indication to MTX. All (n=3) of the high-risk patients were treated with EMA-CO chemotherapy. Median duration of chemotherapy resulting in normalization of BHCG was 4 (1–16) weeks. Ten (42%) patients had a resistance to IM-MTX and were treated with Actinomycin (n=5) or EMA-CO (n=5) chemotherapy. Median duration for normalization of serum BHCG with second line chemotherapy was 16 (4–22) weeks. Four of 5 patients treated with actinomycin in second line needed EMA-CO chemotherapy as a third line because of the lack of response. All of patients had a complete response to chemotherapy. Conclusion: GTD is a disease of young women. Most were diagnosed with low risk disease and complete mole. Most patients achieved complete response with first line chemotherapy. IM-MTX resistance was noted in 42% patients but achieved a complete response with second- or third-line chemotherapy.